FAPE and LRE in Online Learning: Special Education Directors’ Perspectives - Greer, Diana; Harvey, Danna; Burdette, Paula; Basham, James (Journal of the American Academy of Special Education Professionals, 2015)
While the provision of a "free appropriate public education" (FAPE) has contributed significantly to the educational experiences of students with disabilities, little is known about how services are actually provided in an online learning setting. Thus, telephone and face-to-face interviews were conducted with state directors of special education from 16 states to explore their knowledge of and experiences with FAPE in online learning. After interviews were transcribed, researchers reviewed 15 transcripts to identify common experiences and issues. Preliminary findings indicate that additional guidance or information is needed about FAPE and how to provide related services in an online environment.